Enhancing farmers' adaptive capacity through economic, political, cultural, and institutional sensitivities to climate change - Suryani Darham; Nik Ahmad Sufian Burhan; Mohd Roslan Rosnon (Penerbit Universiti Kebangsaan Malaysia, 2025)
This conceptual paper investigates how economic, political, cultural, and institutional responses to climate change shape farm-level adaptive capacity, thereby influencing farmers' resilience to climate shocks. Instead of conducting a systematic literature review, the study combines theoretical and contextual insights to present a multidimensional framework that connects social and institutional sensitivities to adaptive behaviours. Economic sensitivity measures farmers' readiness and ability to manage financial risks through diversification, insurance, and investment in resilient practices. Political sensitivity influences public perceptions of climate action, trust in governance, and the ability of policy frameworks to mobilise resources for adaptation. Cultural sensitivity emphasises the importance of traditional knowledge, indigenous practices, and social cohesion in developing collective resilience in farming communities. Institutional sensitivity emphasises the importance of policies, organisational support systems, and stakeholder engagement in promoting equitable and long-term adaptation strategies. By combining these four dimensions, the framework provides a comprehensive perspective on how farmers perceive, interpret, and respond to climate-related risks. It emphasises that adaptation is not just a technical response, but a socially embedded process influenced by values, governance, and resource availability. The proposed framework serves as a theoretical foundation for future empirical research on climate adaptation and agricultural resilience, as well as for the development of context-sensitive policies.